Internal medicine rounding practices and the accreditation council for graduate medical education core competencies. Issue 4 (3rd February 2014) - Shoeb, Marwa; Khanna, Raman; Fang, Margaret; Sharpe, Brad; Finn, Kathleen; Ranji, Sumant; Monash, Brad
<x xml:space="preserve">Abstract</x> BACKGROUND The Accreditation Council for Graduate Medical Education (ACGME) has established the requirement for residency programs to assess trainees' competencies in 6 core domains (patient care, medical knowledge, practice‐based learning, interpersonal skills, professionalism, and systems‐based practice). As attending rounds serve as a primary means for educating trainees at academic medical centers, our study aimed to identify current rounding practices and attending physician perceived capacity of different rounding models to promote teaching within the ACGME core competencies. METHODS We disseminated a 24‐question survey electronically using educational and hospital medicine leadership mailing lists. We assessed attending physician demographics and the frequency with which they used various rounding models, as defined by the location of the discussion of the patient and care plan: bedside rounds (BR), hallway rounds (HR), and card‐flipping rounds (CFR). Using the ACGME framework, we assessed the perceived educational value of each model. RESULTS We received 153 completed surveys from attending physicians representing 34 institutions. HR was used most frequently for both new and established patients (61% and 43%), followed by CFR for established patients (36%) and BR for new patients (22%). Most attending physicians indicated that BR and HR were superior to CFR in promoting the following ACGME competencies: patient care, systems‐based practice, professionalism, and interpersonal skills. CONCLUSIONS HR is the most commonly employed rounding model. BR and HR are perceived to be valuable for teaching patient care, systems‐based practice, professionalism, and interpersonal skills. CFR remains prevalent despite its perceived inferiority in promoting teaching across most of the ACGME core competencies. Journal of Hospital Medicine 2014;9:239–243. © 2014 Society of Hospital Medicine